METODE GAUSS-SEIDEL PREKONDISI UNTUK MENCARI SOLUSI SISTEM PERSAMAAN LINEAR - Sativa, Alhumaira Oryza; Putra, Supriadi; ', Zulkarnain (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
This article discusses how to nd a solution of linear system of equations Ax = b, with A in the form of Z -matrix, using preconditioned Gauss-Seidel method. Pre-condition matrix used is the matrix proposed by J.H. Yun [Applied Mathematics Letters, 27: 207-215 (2012)]. Analytically it is shown that the spectral radius ofthe iteration matrix of the preconditioned Gauss-Seidel method is smaller than that of the standard Gauss-Seidel method. Furthermore, from the numerical experiment in solving a linear system of equation Ax = b, it is seen that the preconditionedGauss-Seidel method requires fewer iterations than standard Gauss-Seidel method.